Regional and national perspectives of China's integration into the WTO: a CGE inquiry with emphasis on the agricultural sector - Diao, Xinshen; Somwaru, Agapi; Tuan, Francis (Wiley, 2003)
China's integration in the World Trade Organization (WTO) is already on its fast track. Understanding the complexity of China's dynamic adjustment resulting from its membership in the WTO and the differential regional impacts within China is very important and poses crucial challenge in evaluating its impacts. In this study, we make an attempt to incorporate seven regional commodity‐detailed models into a dis‐aggregated multi‐sector and multi‐region China Computable General Equilibrium (CGE) framework. This framework has allowed us to evaluate the impacts of China's integration into the WTO at both national and regional levels and analyze the inter‐linkages between China's provincial agricultural markets. Using the framework and assumptions about factor mobility, we assess the impacts on China's agricultural and non‐agricultural sectors (regionally and nationally) by reduction of its trade policy distortions, such as tariffs rate changes and quantitative restrictions. We also evaluate the structural changes on China's national and regional production and trade as China implements its commitments and moves into the WTO.